2013
DOI: 10.1007/s13224-013-0407-1
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Trial Using Mifepristone and Vaginal Misoprostol in Termination of Pregnancies up to 63 Days of Gestation

Abstract: Medical abortion with 200 mg oral mifepristone and 800 mcg vaginal misoprostol is an effective, safe, reliable, and noninvasive method with a success rate of 95.65 %. The availability of this low-cost medical treatment using agents which do not require special cold storage and transport facilities and negligible operating theater time makes this provision of safe abortion feasible in settings especially of developing countries, like India, where medical facilities are limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Kumar S et al, found complete abortion by medical abortion in 95.6% of patients. 6 Similarly, Grossman D et al, found complete abortion rate by medical abortion in 93.8% of cases. 7 Silvestre L et al, and Nicholas CW Hill, studied different prostaglandin composition with mifepristone and found similar efficacy of different regimes.…”
Section: Discussionmentioning
confidence: 93%
“…Kumar S et al, found complete abortion by medical abortion in 95.6% of patients. 6 Similarly, Grossman D et al, found complete abortion rate by medical abortion in 93.8% of cases. 7 Silvestre L et al, and Nicholas CW Hill, studied different prostaglandin composition with mifepristone and found similar efficacy of different regimes.…”
Section: Discussionmentioning
confidence: 93%
“…Midlevel provision of medical and aspiration abortion has been shown to be feasible in India, and amendments to the law to approve midlevel provision of abortion care services are currently under consideration by the Ministry of Health and Family Welfare [ 12 , 13 ]. Medical abortion using mifepristone and misoprostol is approved in India up to 63 days of gestation, and has been shown to be safe, reliable and effective [ 14 ], but awareness and knowledge is generally low among women and physicians, and implementation has been slow, especially in the public sector [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%